1996
DOI: 10.1097/00005392-199609000-00050
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Bladder Outlet Obstruction and Lower Urinary Tract Symptoms as Measured by the International Prostate Symptom Score

Abstract: Purpose: We studied the relationship between lower urinary tract symptoms as measured by the international prostate symptom score (I-PSS) and urodynamic findings in elderly men.Materials and Methods: We evaluated 803 consecutive patients with lower urinary tract symptoms via the I-PSS and urodynamics with pressure-flow studies.Results: A statistically significant correlation was found between all I-PSS questions (except intermittency) and objective parameters of obstruction. However, the clinical significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 12 publications
0
29
0
3
Order By: Relevance
“…Some authors, besides, found variability between consecutive flow measurements and circadian changes in various voiding parameters, and particularly in maximum flow rate. 2,3 Therefore, any decision based on a single-flow measurement is questionable, since a natural situation is recommended when using uroflowmetry to depict a patient's normal voiding pattern. Data from a homebased portable flowmeter may accomplish this objective.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors, besides, found variability between consecutive flow measurements and circadian changes in various voiding parameters, and particularly in maximum flow rate. 2,3 Therefore, any decision based on a single-flow measurement is questionable, since a natural situation is recommended when using uroflowmetry to depict a patient's normal voiding pattern. Data from a homebased portable flowmeter may accomplish this objective.…”
Section: Introductionmentioning
confidence: 99%
“…Si como sabemos los síntomas irritativos surgen como respuesta secundaria de la vejiga (inestabilidad del detrusor) al componente obstructivo del proceso, los diferentes cuadros que se presentaron corresponderían a diferentes estadios en el crecimiento de la próstata sin que esto prediga necesariamente el grado de obstrucción como ya ha sido visto (33,37).…”
Section: Discussionunclassified
“…At present, the most utilized method to confirm infravesical obstruction is the pressure / flow study (12)(13)(14)(15)(16). Urodynamics distinguish low flow secondary to hypoactivity of the detrusor from the low flow caused by obstruction.…”
Section: Discussionmentioning
confidence: 99%